Using Lower Amplitudes to Maintain Effective High Dose Spinal Cord Stimulation Therapy (SCS Dosing Pilot Study). Issue 3 (18th September 2020) - El‐Naggar, Amr O.; Reis, Christopher L.; Hatheway, John A.; Schmidt, Todd E.; Pico, Tristan C.; Sanapati, Mahendra R.; Abd‐Elsayed, Alaa; Patel, Amit S.; Calodney, Aaron; Johanek, Lisa; Tan, Ye; McCammon, Sheryl
Abstract: Background: Spinal cord stimulation is an effective therapy for chronic back and/or leg pain. Amplitude dose–response studies are lacking; therefore, little guidance exists regarding the minimum amplitude requirements with specific high dose parameters. This study characterized the minimum amplitude level that maintained SCS therapy satisfaction and pain relief when stimulating at 1000 Hz and 90 μsec. Materials and Methods: Qualified patients had back and leg pain, an implanted neurostimulator programmed to 1000 Hz and 90 μsec, and were very or somewhat satisfied with the therapy, and an average overall VAS pain score ≤ 4 from a daily diary. Patients received four blinded amplitudes (titrated from 80%, 60%, 40%, and 20% of baseline perception threshold), approximately two weeks each, with 1000 Hz and 90 μsec and position‐adaptive stimulation enabled. Patients' satisfaction and overall VAS pain scores were collected for each period. All patients continued through the study, even after reporting lack of therapy satisfaction or pain relief. Results: The minimum amplitude, which maintained therapy satisfaction, was 80% of perception threshold for two patients, 60% for one patient, and 20% for 21 patients. Additionally, six patients lost satisfaction changing from their baseline amplitude to 80% perception threshold. The minimum amplitude level, which maintained overall pain relief, was 80% perception threshold for three patients, 60% perception threshold for one patient, 40% perception threshold for two patients, and 20% perception threshold for 19 patients. Five patients required the setting they were programmed to during the baseline period. Conclusion: The qualified study patients defined an implanted population reporting good pain relief and satisfaction using HD SCS therapy at baseline. The majority of these patients were able to maintain therapy satisfaction and pain relief (70% and 63.3%, respectively) with 20% perception threshold amplitude. Amplitudes below perception threshold could potentially maintain effective SCS therapy with HD stimulation in a subset of patients.